2011
DOI: 10.1029/2010tc002821
|View full text |Cite
|
Sign up to set email alerts
|

The Calabrian Arc subduction complex in the Ionian Sea: Regional architecture, active deformation, and seismic hazard

Abstract: [1] We analyzed the structure and evolution of the external Calabrian Arc (CA) subduction complex through an integrated geophysical approach involving multichannel and single-channel seismic data at different scales. Pre-stack depth migrated crustal-scale seismic profiles have been used to reconstruct the overall geometry of the subduction complex, i.e., depth of the basal detachment, geometry and structural style of different tectonic domains, and location and geometry of major faults. High-resolution multich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
308
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(326 citation statements)
references
References 104 publications
16
308
2
Order By: Relevance
“…In this section we summarize the overall architecture and evolution of the CA subduction complex as derived from an integrated geophysical approach involving the analysis of seismic data at different scales (Polonia et al, 2011). Such architecture and evolution of the CA constitute the structural and geodynamic basis for the present study.…”
Section: The Submarine Subduction Complexmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section we summarize the overall architecture and evolution of the CA subduction complex as derived from an integrated geophysical approach involving the analysis of seismic data at different scales (Polonia et al, 2011). Such architecture and evolution of the CA constitute the structural and geodynamic basis for the present study.…”
Section: The Submarine Subduction Complexmentioning
confidence: 99%
“…Shaded relief morpho-bathymetric map compiled using data collected during different cruises by the CIESM/IFREMER Medimap group (Loubrieu et al, 2008). Major faults derived from the tectonic model of Polonia et al (2011) are indicated and labelled STEP, Splay-1, -2, -3, while the thick, discontinuous, NW-SE trending orange lines offshore the Messina Straits represent the boundary between the two lobes, which is marked by a diffuse area of deformation related to scarps, ridges and troughs. Seismic data from the different datasets used in this work are represented by red, blue and green lines.…”
Section: Splay Fault Systemmentioning
confidence: 99%
See 3 more Smart Citations